Nurturing emotional intelligence through literature - Ghosn, Irma K. (2001)
This article discusses the use of literature in a language class as a way to develop emotional intelligence in children. The author suggests that literature can be motivating and can provide a low-anxiety context for children to learn English. Several response activities are suggested to develop language skills and nurture emotional intelligence. These activities include scripting, detecting feelings in text, a feeling hunt, creating a positive language dictionary, diary entries, and letters to characters.